Diagnostic Accuracy and Clinical Implications of Translabial Ultrasound for the Assessment of Levator Ani Defects and Levator Ani Biometry in Women With Pelvic Organ Prolapse: A Systematic Review. Issue 6 (November 2017) - Notten, Kim J.B.; Vergeldt, Tineke F.M.; van Kuijk, Sander M.J.; Weemhoff, Mirjam; Roovers, Jan-Paul W.R.
Abstract : Objective: The aim of this study was to assess the diagnostic accuracy and clinical implications of translabial 3-dimensional (3D) ultrasound for the assessment of levator ani defects and biometry in women with pelvic organ prolapse (POP). Methods: We performed a systematic literature search through computerized databases including MEDLINE (via PubMed), EMBASE (via OvidSP), and the Cochrane Library using both medical subject headings and text terms from January 1, 2003, to December 25, 2015. We included articles that reported on POP status and diagnostic accuracy measurements with translabial 3D ultrasound or transperineal ultrasound for the detection of levator ani defects or for measuring pelvic floor biometry, that is, levator ani hiatus, or reported on the clinical relevance of using translabial 3D ultrasound for levator ani defects or measuring pelvic floor biometry in women with POP. Results: Thirty-one articles were selected in accordance with parts of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines that can be applied to studies of diagnostic accuracy. Twenty-two articles (71%) are coauthored by 1 expert in this field. Detecting levator ani defects with translabial 3D ultrasound compared with magnetic resonance imaging showed a moderate to good agreement, whereas measuring hiatal biometry on translabial 3D ultrasound compared with magnetic resonance imaging showed a moderate to very good agreement. The interobserver agreement for diagnosing levator ani defects and measuring the levator hiatal area showed a moderate to very good agreement. Furthermore, levator ani defects increase the risk of cystocele and uterine prolapse, and levator ani defects are associated with recurrent POP. Finally, a larger hiatus was associated with POP and recurrent POP. Conclusions: Translabial 3D ultrasound is reproducible for diagnosing levator ani defects and ballooning hiatus. Both levator ani defects and a larger hiatal area are, in a selected population of patients with pelvic floor dysfunction, associated with POP and recurrent POP. More research is needed concerning external validation because most data in this article are coauthored by 1 expert in this field. Abstract : Translabial ultrasound for the assessment of levator ani defects and levator ani biometry in women with pelvic organ prolapse: a systematic review.